Application of the small punch creep test in predicting creep properties of grade 91 steel - Ferdous, I. U.; Nasrul Azuan, Alang; Juliawati, Alias; Norhaida, Ab Razak (Springer US, 2024)
This study evaluates the effectiveness of small punch creep testing (SPCT) as an alternative to conventional uniaxial creep testing (UCT) in predicting creep properties for Grade 91 steel. Cylindrical specimens extracted longitudinally from an as-received Grade 91 pipe were subjected to UCT at 600 °C under the stress level of 160-190 MPa. Equivalent SPCTs utilized a custom-designed rig to test 0.5-mm-thick, 8-mm-diameter disc specimen at 600 °C under the load level of 400-475 N loads. Both test types exhibited typical primary, secondary, and tertiary creep regimes. A correlation factor of 2.5 provided excellent agreement between SPCT and UCT rupture times. Converting SPCT punch displacement rates to equivalent minimum creep strain rates enabled application of established creep models like Monkman–Grant and Norton for long-term rupture life prediction. The Larson–Miller approach successfully correlated short-term SPCT data for long-term rupture life extrapolation. Minimum creep strain rate versus stress trends from UCT aligned well with equivalent rates from SPCT data. Fractographic analysis revealed similar ductile, dimple-dominated fracture morphologies in both test types. This study validates SPCT as an efficient methodology for creep assessment using minimal material volumes.